Operational Excellence and Sustainable Business Performance: Operational Performance Mediation in Indonesian Manufacturing Firms - Basuki Fabina; Galih Raspati; Yoki Muchsam (Information Technology and Science (ITScience), 2026)
Sustainable business performance has become a strategic priority for manufacturing firms as increasing environmental regulations and competitive pressures require organizations to integrate operational efficiency with sustainability objectives. However, previous studies have largely examined the direct relationship between operational excellence and sustainable business performance, while limited attention has been given to the mediating role of operational performance in this relationship, particularly within emerging economies. This study aims to examine the effect of operational excellence on sustainable business performance and to investigate the mediating role of operational performance among manufacturing firms in Indonesia. A quantitative explanatory research design was employed using survey data collected from 312 medium and large-scale manufacturing companies in West Java. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that operational excellence has a significant positive effect on sustainable business performance and significantly enhances operational performance. Furthermore, operational performance positively influences sustainable business performance and mediates the relationship between operational excellence and sustainable business performance. These findings support the Resource Based View by demonstrating that operational capabilities create sustainable competitive advantages when translated into superior operational outcomes. The study contributes to the sustainability and operations management literature by clarifying the capability building mechanism linking operational excellence to sustainable business performance in an emerging economy context. Managerially, the findings suggest that manufacturing firms should strengthen operational execution capabilities through continuous improvement, process standardization, and operational efficiency initiatives to achieve long-term sustainability.